“ATemp”, A Tempe-based product with High Nutritional Value and Low Glycemic Index (Alternative Plant-Based Protein Sources for Diabetic Patients) - Rumahorbo, Hotma; Saleky, Yohannes Willihelm; Lucas, Jedya; Herdianta, Dhimas (Poltekkes Kemenkes Palu, 2024)
Diabetes Mellitus (DM) is a metabolic endocrine disease with the identical symptom of hyperglycemia. One of the main pillars in DM management is nutrition therapy through limiting the intake of carbohydrates and high simple sugar (monosaccharides). The availability of foods with low glucose levels has become one of the crucial needs of DM patients in controlling blood glucose levels. Tempeh is a soy-fermented local food that has been known widely by Indonesian Society. Tempeh-based food products with high nutritional value and low sugar are still scarcely found in society. Thus, this research aims to develop a tempeh-based product with high nutrition value (protein), low Glycemic Index (GI) level and adequate fibre content. Research and Development Design method was used in this research with the selecting, sorting and processing done with respecting the standard of food processing. The yield product was tested on 40 panellists for organoleptic tests, analyzed in the laboratory to measure the nutrient content, and calculated for glycemic index. The results show that “ATemp” (a tempeh floss) has a result of organoleptic test with the panellist who stated like and very like for colour of the product 65%, for the aroma 67,5%, for the texture 58% and for the taste of the product 50%. Laboratory analysis has shown that 100 g of ATemp contains 23 g of fat, 19 g of protein, 45 g of carbohydrate, 1 g of sugar, 257 mg of sodium, 12 g of fibre and 465 kcal of total energy. The result of GI test shows that Atemp has a GI level of 12 (low) and GL level of 2,7 (low). ATempt has a high potential to be an alternative food for diabetes or for those who are doing low-sugar diet.